Comparison of C- Reactive Protein (CRP) Analysis Agglutination Method and Floresense Immunoassay in Smokers at PT. Anugerah Santosa Abadi Surabaya - Wahyuni, Sri; Ismawatie, Emma; Maulani, Yulita (Rifa'Institute, 2024)
Introduction: Smoking has detrimental consequences on the development of diseases with inflammatory components, which cause tissue damage and cause the body to secrete more C-Reactive Protein (CRP). To ensure accurate diagnosis, a variety of techniques, including the latex agglutination method and the Fluorescence Immunoassay (FIA), are available for measuring CRP levels in human blood. Objective: This research is comparing the results of CRP testing performed on smokers at PT. ASA, Surabaya using the agglutination method and the FIA. Method: This research is analytic research with a cross sectional design. This research conduct in PT. ASA, Surabaya from May to June 2023. Result and Discussion: The results show that the CRP agglutination method shows negative results in 27 people (90%). Most of the CRP examination results using the FIA method show negative results in 27 people (90%). Conclusion: Diagnostic test for CRP agglutination using the FIA method obtain a sensitivity of 100% and a specificity of 100%. We can conclude that, there is no difference in CRP levels between the agglutination method and FIA